Pengembangan Chatbot Berbasis Rule-based Pada Website Penerimaan Mahasiswa Baru Universitas Almuslim - Anang Kurniawan; Dedy Armiady; Zulkifli Zulkifli (Jurnal Ilmu Komputer Aceh, 2025)
Almuslim University, as one of the best private universities (PTS) in Aceh, provides information services regarding new student admissions. However, prospective students often face difficulties in obtaining quick and accurate responses due to limited time and resources from the admission committee. To address this issue, this study develops a rule-based chatbot that can automatically provide information and allows prospective students to contact an admin if needed, without requiring third-party applications. The aim of this research is to develop a rule-based chatbot system to automatically answer questions from prospective students and make the service available 24/7. The system is designed using the Agile development method, enabling flexible and iterative development. The chatbot operates based on keyword matching stored in the database to generate appropriate responses. The system also features typo correction, suggestions for similar questions, and user satisfaction rating after several interactions. Additionally, conversation history is recorded for analysis purposes, and a live chat option with an admin is available when the chatbot’s response is insufficient. The testing results show that the system can answer most user questions accurately and improve the efficiency of interactions without requiring direct admin involvement. Therefore, this chatbot serves as an effective and scalable solution for digital information services